Those who know don't say: the Nation of Islam, the black freedom movement, and the carceral state - Felber, Garrett (Justice, power, and politics, 2020)
The making of the "Black Muslims" -- Shades of Mississippi -- Whose law and what order? -- You're brutalized because you're black -- The state the state produced.